Modeling Root-Knot Nematode Regulation by the Biocontrol Fungus Pochonia chlamydosporia - Ciancio, Aurelio; Cabrera, Ileana Miranda; Hidalgo-Diáz, Leopoldo; Puertas, Ana; Duvergel, Yoannia Castillo (Frontiers in Fungal Biology, 2022)
Two models of increasing complexity were constructed to simulate the interactions between the root-knot nematode (RKN) Meloidogyne incognita and the biocontrol fungus Pochonia chlamydosporia var. catenulata in a rhizosphere microcosm. The models described discrete population dynamics at hourly rates over a 6-month period and were validated using real parasitism and nematode or fungus data. A first, general Pochonia–nematode–root model (GPNR) used five functions and 16 biological constants. The variables and constants describing the RKN life cycle included the rates of egg production, hatching, juvenile (J2), and mature female development, including root or nematode self-density-dependent factors. Other constants accounted for egg parasitism, nematode-induced root losses, growth, and mortalities. The relationship between nematodes and fungal propagules showed density dependence and cyclic variations in time, including an attractor on the propagules and J2 phases space. The simulations confirmed a P. chlamydosporia optimal initial density of 5 · 103 propagules · cc soil-1, as usually applied in assays. The constants used in GPNR showed adherence to the nematode biology, with 103 eggs per egg mass, a 10-day average lifespan of J2, with 2 days required to enter roots, and adult lifespan lasting 24 days. The fungus propagule lifespan was 25 days, with an average feeder root lifespan lasting around 52 days. A second, more complex Pochonia–nematode–root detailed model (GPNRd) was then constructed using eight functions and 23 constants. It was built as GPNR did not allow the evaluation of host prevalence. GPNRd allowed simulations of all RKN life stages and included non-parasitic and parasitic fungus population fractions. Both GPNR and GPNRd matched real J2 and fungus density data observed in a RKN biocontrol assay. Depending on the starting conditions, simulations showed stability in time, interpreted as effective host regulation. GPNRd showed a fungus cyclic relationship with the J2 numbers, with prevalence data close to those observed (38.3 vs. 39.4%, respectively). This model also showed a further density-independent nematode regulation mechanism based on the P. chlamydosporia switch from a non-parasitic to a parasitic trophic behavior. This mechanism supported the biocontrol of M. incognita, also sustained by a concomitant increase of the root density.